2023
DOI: 10.1021/acs.iecr.3c01560
|View full text |Cite
|
Sign up to set email alerts
|

Universal Model for Predicting Maximum Spreading of Drop Impact on a Smooth Surface Developed Using Boosting Machine Learning Models

Jiguo Tang,
Shengzhi Yu,
Xiaofan Hou
et al.

Abstract: Drop impact on a solid surface is a fundamental phenomenon in nature and engineering. Prediction of the maximum spreading ratio during drop impact is critical for modeling and optimizing the relevant processes. However, accurately modeling the maximum spreading using empirical and numerical methods remains challenging. Machine learning (ML) has recently provided a promising way to understand and model complex fluid phenomena. Thus, in this study, a universal model is developed by using machine learning methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Regarding rough and superhydrophobic surfaces, Wang et al found that surface roughness minimally affects the spreading diameter of dilute SDS droplets on micropillared arrays . However, higher surfactant concentrations decrease the droplet-receding velocity and can prevent bouncing on superhydrophobic surfaces. ,, Additionally, surfactant molecules entering micro or nanostructures on superhydrophobic surfaces change the surface wettability, with faster impact speeds enhancing this interaction. Efforts at developing a prediction of maximum spreading ratios are numerous and take into account a variety of variables (fluid properties or wetting characteristics) but generally do not account for the unique properties of surfactant-laden liquids. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding rough and superhydrophobic surfaces, Wang et al found that surface roughness minimally affects the spreading diameter of dilute SDS droplets on micropillared arrays . However, higher surfactant concentrations decrease the droplet-receding velocity and can prevent bouncing on superhydrophobic surfaces. ,, Additionally, surfactant molecules entering micro or nanostructures on superhydrophobic surfaces change the surface wettability, with faster impact speeds enhancing this interaction. Efforts at developing a prediction of maximum spreading ratios are numerous and take into account a variety of variables (fluid properties or wetting characteristics) but generally do not account for the unique properties of surfactant-laden liquids. …”
Section: Introductionmentioning
confidence: 99%
“… 43 46 Efforts at developing a prediction of maximum spreading ratios are numerous and take into account a variety of variables (fluid properties or wetting characteristics) but generally do not account for the unique properties of surfactant-laden liquids. 47 49 …”
Section: Introductionmentioning
confidence: 99%